Alkaloids from Alstonia scholaris and Ficus schwarzii - Krishnan, Premanand (2022)
Alkaloids, which are the most studied secondary metabolites, are structurally diverse and well known for their biological activity. The aim of the present study is to perform phytochemical investigations on the alkaloidal composition of two selected plant species, namely, Ficus schwarzii (Moraceae) and Alstonia scholaris (Apocynaceae). (specimen from the West Coast of Peninsular Malaysia). The previously unexplored phytochemistry of F. schwarzii and the phytochemical variation of A. scholaris due to locality have motivated research into the two species collected from Peninsular Malaysia.